CEGAH OSTEOPOROSIS MELALUI PELATIHAN SENAM LANSIA DAN CERAMAH KESEHATAN DI DESA TANJUNG GUSTA - Saharnauli Janna Verawaty Simorangkir; Novita Hasiani Simanjuntak (P3M Universitas Aisyiyah Surakarta, 2023)
Osteoporosis is a systemic bone disorder, which is characterized by damage to the micro-architecture of bone tissue, which occurs as a result of an imbalance in the bone remodeling process. Various actions that can be taken to prevent osteoporosis one of which is to increase physical activity such as exercise. Exercise can stimulate bone growth and maintain bone mass. The series of activities carried out were training in elderly gymnastics at the beginning of the event, then followed by providing counseling about Osteoporosis using the health lecture method. The purpose of this activity was to provide education about osteoporosis and to train elderly gymnastic movements as a step to prevent osteoporosis. This activity was attended by 30 participants in Dusun II Timur, Tanjung Gusta Village, all of whom were female. The results of this activity showed that as many as 22 people (73.3%) participants showed an increase in test results, and the results of the paired t test showed a significant difference between the pretest and posttest results with a p value <0.05, meaning that this activity was effective in terms of increasing knowledge about Osteoporosis in all participants